Biohydrogen production potential of R. palustris CGA009 by photofermentation of liquid hydrolysate obtained from steam explosion of BSG - Mabutyana, Luntu (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.